Associations between reading and writing postures and myopia among school students in Ningbo, China - Jiang, Danjie; Shi, Bijun; Gao, Hua; Guo, Yanbo; Zhou, Shaoying; Zhang, Yan (Frontiers in Public Health, 2022)
Background: We conducted this study to examine the prevalence of myopia among school students in Ningbo, and to explore the associations between reading and writing posture and myopia. Methods: A population-based and cross-sectional investigation was performed and 3256 school students aged 8 to 19 years old were recruited. Each enrolled subject underwent uncorrected distance visual acuity (UDVA) assessment using a standard logarithmic visual acuity E chart and non-cycloplegic autorefraction examination. Self-administered questionnaires were used to investigate myopia-related reading and writing posture and behavior habits. Results: Myopia prevalence of primary school students, middle school students and high school students were 61.49%, 81.43% and 89.72%, respectively. In the associations between reading and writing posture and myopia, we identified that a reading distance >33 cm is a protective factor of myopia in female students (OR = 0.31, 95% CI = 0.15-0.64), both in primary (OR = 0.55, 95% CI = 0.30-0.99) and middle school students (OR = 0.37, 95% CI = 0.15-0.90). Conclusions: Reading distances > 33 cm may be used as an additional measure for myopia prevention and control. Educational and public health benefits may arise from appropriate reading and writing posture measures.